2019
DOI: 10.1021/acs.jced.9b00046
|View full text |Cite
|
Sign up to set email alerts
|

Density and Viscosity of Magnesium Chloride Solution in N-Methylacetamide over the Temperature Range from 308.15 to 328.15 K at Ambient Pressure

Abstract: The values of densities in N-methylacetamide solutions of magnesium chloride have been measured at atmospheric pressure using an Anton Paar DMA 5000M high-precision vibrating U-tube densimeter at temperatures ranging from 308.15 to 328.15 K, ΔT = 5 K, and in the concentration range from 0 to 0.083 mol·kg–1. The kinematic viscosity for these mixtures has been measured at the same thermodynamic conditions using an Ubbelohde viscometer. Partial molar volumes of N-methylacetamide, partial molar volumes of magnesiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The standard uncertainties in the refractive index and temperature are ±0.0004 and ±0.02 K, respectively. The ρ, u , η, and n D for the pure liquids obtained in this work are compared with the corresponding literature values at investigated temperatures and are reported in Table , which are in good agreement with literature values.…”
Section: Experimental Sectionsupporting
confidence: 84%
See 1 more Smart Citation
“…The standard uncertainties in the refractive index and temperature are ±0.0004 and ±0.02 K, respectively. The ρ, u , η, and n D for the pure liquids obtained in this work are compared with the corresponding literature values at investigated temperatures and are reported in Table , which are in good agreement with literature values.…”
Section: Experimental Sectionsupporting
confidence: 84%
“…The experimentally measured values of densities, ρ, ultrasonic speeds, u, viscosities, η, and refractive indices, n D , of [Bmim][BF 4 ] and NMA solution as a function of mole fraction, x 1 of the IL, and temperature are given in Table 3 26,32 1362 27 3.312 31 0.9468 33,34 1347.6 34 3.2310 33 0.94624 35 1354.28 35 3.6648 34 0.94571 36 3.38 35 0.9588 37 3.4878 36 3.012 30 1.4257 30 0.9438 27 1339.48 35 3.1020 33 1.4230 33 0.9415 30,34 3.1025 34 0.9405 33 3.004 35 0.94224 35 3 measured with a highly accurate Abbemat HP refractometer (RXA170, Anton Paar) with a built-in temperature controller, whereas the conventional Abbe refractometer used in the literature work in comparison may not be highly accurate. It is observed that the experimental values are in reasonable agreement with the literature.…”
Section: Resultsmentioning
confidence: 99%
“…N-methylacetamide (Sigma-Aldrich, mass fraction ≥0.99 as stated by the supplier) was purified by boiling with calcium oxide and double distillation under vacuum (the boiling point was about 358 K). 29 The water content was determined with the Karl Fisher method titration and did not exceed 50 ppm. Freshly bidistilled and deionized water (with specific conductivity of about 2 × 10 −4 S m −1 ) was used for the preparation of solutions.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the reagents used are presented in Table . N -methylacetamide (Sigma-Aldrich, mass fraction ≥0.99 as stated by the supplier) was purified by boiling with calcium oxide and double distillation under vacuum (the boiling point was about 358 K) . The water content was determined with the Karl Fisher method titration and did not exceed 50 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of intermolecular interactions play an important role in understanding the interactions that take place in solutions. Changes in density, viscosity, ultrasound velocity and other parameters from temperature and concentration have been considered by many scientists and shed light on the structural changes occurring in solutions [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%